Practical experience of ustekinumab in patients with moderate-to-severe psoriasis who had inadequate therapeutic response to previous tumor necrosis factor blockers - Tzu-Chang Wang; Hsien-Yi Chiu; Ting-Shun Wang; Tsen-Fang Tsai (Wolters Kluwer Medknow Publications, 2015)
Background/Objective(s): Few studies have evaluated the therapeutic response among switchers of biologics in patients with psoriasis. We report our experience of ustekinumab in patients with psoriasis who did not respond adequately to tumor necrosis factor (TNF) blockers treatment previously. Methods: We retrospectively reviewed the therapeutic response of 20 patients with moderate-to-severe psoriasis who had failed conventional treatment and had inadequate therapeutic response to previous etanercept and/or adalimumab between 2012 and 2013. Inadequate therapeutic response is defined by <50% improvement in Psoriasis Area and Severity Index (PASI) compared to baseline. Ustekinumab 45 mg was given at Week 0, Week 4, and Week 16, and patients were evaluated for safety and effectiveness at Week 0, Week 4, Week 16, and Week 28. Results: Nineteen patients were followed to Week 16, and 14 patients to Week 28. At Week 16, at least PASI 90, PASI 75, PASI 50, and PASI 25 responses were seen in three patients (3/19, 16%), four patients (4/19, 26%), seven patients (7/19, 37%), and 13 patients (13/19, 68%), respectively. At Week 28, at least PASI 90, PASI 75, PASI 50, and PASI 25 responses were seen in two patients (2/14, 14%), three patients (3/14, 21%), seven patients (7/14, 50%), and 11 patients (11/14, 79%), respectively. No severe adverse events were recorded in our series. Conclusion: Despite a less favorable response compared to the pivotal studies, at least PASI 50 response was achieved in 50% of patients at Week 28 after three injections of ustekinumab without serious adverse events.